"I Like Your Suggestion!" the role of humanlikeness and parasocial relationship on the website versus voice shopper's perception of recommendations. Issue 4 (10th December 2020) - Whang, Claire; Im, Hyunjoo
Abstract: Voice assistants are changing the way consumers shop. Guided by the anthropomorphism literature and parasocial interaction theory, this study investigated how the new unique relationship between consumers and artificial intelligence‐powered voice assistants may affect the way consumers evaluate the recommended products through two experiments. Study 1 ( n = 85, students) employed a 2 (shopping medium type: voice assistant vs. website) × 2 (interaction style: task‐oriented vs. socially‐oriented) between‐subjects design lab experiment. Study 2 ( n = 418, Mechanical Turk) employed a 2 (shopping medium type: voice assistant vs. website) × 2 (product type: search vs. experience) between‐subjects online experiment. The results suggested that consumers may perceive voice assistants as pseudohuman agents detached from the service provider while perceiving websites as a tool or interface used by the provider, resulting in a more positive perception and evaluation of websites. As one of the few studies investigating voice assistants from the consumer perspective, this study contributes to the growing body of research in voice assistants. The study also contributes to anthropomorphism literature and parasocial interaction theory by confirming the causal relationship between humanlikeness and parasocial relationships.